WOMEN'S LEADERSHIP STRATEGIES TO ADVANCE THE PHARMACEUTICAL BUSINESS IN INDONESIA : AN ETHNOGRAPHIC PERSPECTIVE - Chairani Harahap; K.P. Suharyono S.Hadiningrat; Jones Zenas Rante (Yayasan Inspirasi Merah Putih Indonesia, 2025)
Efforts to advance public welfare through industrial development require penta-helix collaboration to achieve goals more effectively and efficiently, especially in the pharmaceutical sector, where raw materials are still dependent on other countries. This poses a shared challenge requiring all elements of the nation, especially the government, to play a significant role in collaborating on all national resources towards independence, sovereignty, and national progress for the welfare of the people. The pharmaceutical sector in Indonesia is experiencing rapid progress, but on the other hand, it requires a focus on gender-based human resource development, particularly women's leadership. In fact, the role of women in the pharmaceutical industry is significant, but opportunities for leadership remain very limited. In general, the number of women holding managerial positions in Indonesia in 2010 was around 12%, increasing to around 20% by 2025. Challenges and obstacles are highly dynamic, influenced by many factors, including traditional customs and the still-low level of education for women. The women's emancipation championed is still enjoyed by elite women, so their roles and contributions are still insignificant. Gender issues in the pharmaceutical industry, particularly female leadership, remain a significant issue. Strategies are needed to address this by improving the quality and quantity of female human resources, enabling them to achieve top career positions. Therefore, this research was conducted using a qualitative descriptive design with an ethnographic approach. The author served as one of the primary informants. Therefore, triangulation of data collection methods was necessary, including interviews, documentation, and the vision and mission of female leadership during the researcher's tenure as CEO of a pharmaceutical company in Indonesia. The collected data were analyzed using qualitative methods to describe the phenomenon using an ethnographic approach, reflecting the researcher's actions during her tenure as CEO. The results revealed that the strategies used by female leadership to advance the pharmaceutical business in Indonesia are as follows: a) Self-confidence, equipped with adequate education and experience; b) Readiness to compete objectively with other leaders and aspiring leaders, both male and female; c) Working hard, intelligently, and prioritizing the company's interests; d) Building a solid team; e) Developing a pentahelix-based network; f) Understanding business changes in the pharmaceutical industry; g) Seeking support from top leaders; h) Developing talented human resources. i) Understanding and applying management and leadership skills from global business leaders; and j) adapting to change, especially in the VUCA era of digital advancement.